The State and Enterprise: Canadian Manufacturers and the Federal Government 1917-1931; Business and Social Reform in the Thirties - Howell, Colin D. (Labour / Le Travail, 1980)
This article reviews the books, "The State and Enterprise: Canadian Manufacturers and the Federal Government 1917-1931," by Tom Treves, and "Business and Social Reform in the Thirties," by Alvin Finkel.